2020
DOI: 10.3390/ijerph17124189
|View full text |Cite
|
Sign up to set email alerts
|

How to Communicate Food Safety after Radiological Contamination: The Effectiveness of Numerical and Narrative News Messages

Abstract: Food risk and the safety of foodstuffs in the aftermath of contamination are highly sensitive issues to communicate. Food risks receive extensive attention from the news media, which requires messages to be carefully drafted to minimize harm and avoid unnecessary boycotts. Once a food risk is deemed eliminated, communication efforts must rebuild trust among consumers. The latter is a particularly difficult task after radiological contamination. This study tests whether numerical messages, narrative messages, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…This overall effect indicates that a specific graphics could produce a positive effect on intended behavior. Providing a graphic is critical both to providing the information needed by the consumer in a simple format [ 42 ] and also provides a meaningful “anchor” that is needed by consumers to help mitigate perceptual bias that can underestimate food safety risk [ 74 ]. Because the graphic was the most prominent feature of the schematics viewed by consumers, its importance, relative to other components in the overall message, could be explained easily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This overall effect indicates that a specific graphics could produce a positive effect on intended behavior. Providing a graphic is critical both to providing the information needed by the consumer in a simple format [ 42 ] and also provides a meaningful “anchor” that is needed by consumers to help mitigate perceptual bias that can underestimate food safety risk [ 74 ]. Because the graphic was the most prominent feature of the schematics viewed by consumers, its importance, relative to other components in the overall message, could be explained easily.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, authors have found differences in the ways in which information is provided in nutrition education displays among older and younger consumers and some ethnic groups [ 40 , 41 ]. Other authors have shown that many consumers preferred a simpler “more detached” approach to understanding food safety risks associated with food radiation risks [ 42 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They saw education from a range of independent sources for consumers as important, and were confident that consumers would become self-informed [ 35 ]. Previous studies have concluded that consumers will view a reduction in the perceived risk once education on the benefits and reassurance about the safety of the technology is provided [ 36 , 37 , 38 ]. In practice, creating a consistent narrative about sustainability and the low-beam nature of the radiation, to alleviate concerns for those who seek more information, needs to be carefully designed by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Under the communication advantages of information technology, it is easy to form stigma, but it is difficult to "destigmatize" and reconstruct trust [20,21].…”
Section: Introductionmentioning
confidence: 99%